The Land of the English Kin : Studies in Wessex and Anglo-Saxon England in Honour of Professor Barbara Yorke - Langlands, Alex; Lavelle, Ryan (2020)
This volume draws together a series of papers that present some of the most up-to-date thinking on the history, archaeology and toponymy of Wessex and Anglo-Saxon England more broadly. In honour of one of early medieval European scholarship’s most illustrious doyennes, no less than twenty-nine contributions demonstrate the indelible impression Barbara Yorke’s work has made on her peers and a generation of new scholars, some of whom have benefitted directly from her tutorage. From the identities that emerged in the immediate post-Roman period, through to the development of kingdoms, the role of the church, and impacts felt beyond the eleventh century, the rich and diverse character of the studies presented here are testimony to the versatility and extensive range of the honorand’s contribution to the academic field.